2012
DOI: 10.1021/jz300362k
|View full text |Cite
|
Sign up to set email alerts
|

System-Dependent Signatures of Electronic and Vibrational Coherences in Electronic Two-Dimensional Spectra

Abstract: In this work, we examine vibrational coherence in a molecular monomer, where time evolution of a nuclear wavepacket gives rise to oscillating diagonal- and off-diagonal peaks in two-dimensional electronic spectra. We find that the peaks oscillate out-of-phase, resulting in a cancellation in the corresponding pump-probe spectra. Our results confirm the unique disposition of two-dimensional electronic spectroscopy (2D-ES) for the study of coherences. The oscillation pattern is in excellent agreement with the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
80
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 28 publications
0
80
0
Order By: Relevance
“…Cross peaks can be signatures of coupling (in several forms) or energy transfer [47,48]. Cross peaks with oscillating amplitudes are most often signatures of intramolecular vibrational modes (vibrational coherence) or strong electronic coupling (electronic coherence) [41,42,[49][50][51][52]. Similar coherent oscillations have been observed in photosynthetic proteins using related techniques as well [53][54][55][56].…”
Section: Introductionmentioning
confidence: 62%
“…Cross peaks can be signatures of coupling (in several forms) or energy transfer [47,48]. Cross peaks with oscillating amplitudes are most often signatures of intramolecular vibrational modes (vibrational coherence) or strong electronic coupling (electronic coherence) [41,42,[49][50][51][52]. Similar coherent oscillations have been observed in photosynthetic proteins using related techniques as well [53][54][55][56].…”
Section: Introductionmentioning
confidence: 62%
“…This conclusion cannot be reached through a diagrammatic analysis alone because there is an implicit assumption that the energy levels are infinitely well defined. 23 However, experimentally, vibronic transitions are always broadened and therefore excitation and detection will always have some detuning. Our experimental result is a clear example of this effect and suggests that interpretations relying solely on phase variations might not always produce correct results.…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…22 Another study using a much simpler isolated chromophore showed that indeed phase shifts between the different peaks on the 2D map are expected, although only 0 o or 180 o degrees phase shifts were forecast and experimentally observed. 23 This assignment method relies on a clear determination of the absorption peak maxima related to the 0-0 transition and the first vibronic transition, 0-1, which is rarely found in solution. A recent theoretical paper proposed that another way to differentiate vibrational from electronic coherences is to measure the relative phase (between diagonal and cross-peaks) as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, electronic transitions are commonly coupled to molecular vibrational modes, and vibrational coherences both in the ground and excited states can be prepared by broadband pulses, in the same way that a coherent superposition of different excitonic or electronic states may be prepared [17]. Recent theoretical and experimental research has explored the different coherence signatures arising in 2D-ES, but for the most part possible effects from the laser spectrum have been neglected [18][19][20][21][22][23][24].…”
mentioning
confidence: 99%